OP0252 Rheumatoid arthritis patients with continued low disease activity have similar outcomes over 10 years, regardless of initial therapy. (15th June 2017) - Bergstra, SA; Landewé, RB; Huizinga, TW; Allaart, CF
Abstract : Background: Low disease activity and remission in rheumatoid arthritis (RA) patients is achieved earlier and in higher frequency when the initial treatment includes a combination of methotrexate (MTX) with corticosteroids or a biologic disease modifying anti-rheumatic drug than MTX alone. However, it is unknown whether in patients with early and persistently good response the initial treatment still has an impact on long term outcomes. Objectives: To compare 10 years disease outcomes of RA patients with persistent low disease activity on MTX monotherapy or on initial combination therapy with infliximab or prednisone and sulfasalazine. Methods: RA patients with 10 years follow-up from the BeSt study were analyzed. RA patients fulfilling the American College of Rheumatology 1987 criteria with <2 years symptom duration were "treated to target" aiming at disease activity score (DAS) ≤2.4, assessed with 3-monthly intervals. Patients in arms 1 and 2 started MTX monotherapy, patients in arm 3 started MTX, sulfasalazine and prednisone and patients in arm 4 started MTX and infliximab. All had DAS≤2.4 from t=6 months until t=10 years and therefore stayed on initial treatment, with patients in arms 3 and 4 tapering to monotherapy within 10 months. Patients in arms 1 and 2 were compared with patients in arms 3 and 4. Between-group differences over time were compared using (generalized) linear mixed model analyses, for the outcomes DAS, Health Assessment Questionnaire (HAQ), erythrocyte sedimentation rate (ESR), visual analogue scale (VAS) patient global health (range 0–100), percentage patients in remission and drug free remission and percentage patients with Sharp/van der Heijde score progression ≥5. Results: At t=10 years 28/247 (11%) patients in arms 1 and 2 had sustained DAS≤2.4 compared to 68/261 (26%) patients in arms 3 and 4. Patients in arms 1 and 2 were less often ACPA positive (46% versus 54%, p=0.477), had shorter symptom duration at baseline [median (range) 14 (1–191) versus 18 (4–263) weeks, p=0.004] and less radiologic damage progression after 10 years [0 (0–16) versus 2.5 (0–26), p=0.014] than patients in arms 3 and 4. No between-group differences were found over time, except for the percentage of patients in drug free remission. Significant group-time interactions were found for DAS, ESR and VAS patient's global health, but not HAQ, percentage remission and percentage drug free remission, with slightly worse results over time for arms 3 and 4 compared to arms 1 and 2 (table 1 ). Conclusions: More patients achieved continuous low disease activity on prednisone or infliximab combination therapy tapered to MTX monotherapy than on MTX monotherapy, but there appear no additional benefits of combination treatment strategies for patients who have sustained DAS≤2.4. Regardless of initial induction therapy, those who remain in low disease activity have similar long term outcomes, with only the proportion of patients in drug free remission being higher in the MTX monotherapy group. These results strongly suggest that rapid achievement of remission/LDA itself, rather than how you achieve it, is crucial for determining long-term outcome in RA. Disclosure of Interest: None declared